Considering the Role of Money and Gifts in the (Re)-construction of Motherhood and Family Among Indonesian Transnational Female Domestic Workers - Diah Irawaty (IKAT: The Indonesian Journal of Southeast Asian Studies, 2021)
Most studies on female migrants as money earners claim that this new context of labor exhibits two distinct realms of either the commodification of love and care or the expression of care where money and emotion intertwine in maintaining family relationships and in creating reciprocity and exchange. I explore different modes of using money and gifts in addition to the major framework of economization of emotion and the emotionalization of money. I differentiate the gifts from money as it refers to non-cash gifts or in-kind gifts. This paper investigates other cultural contexts and social-political dynamics that possibly induce the construction of different roles of money and gifts. It assesses the kinship strategies and mechanisms female migrants, and their stayed-behind children develop in response to physical separation by sending money and gifts and their resistance to the state’s dominant version of the family and money. This paper elaborates how money and gifts connect to women’s identity as transnational mothers to redefine their parenting roles as main economic providers and their identity as transnational family members. It has some bearing on creating a new identity as women that might be not akin to the state’s gender politics and the politics of family as well as state maternalism. The study interrogates how sending and receiving money and gifts in a transnational family engenders transformation in the construction of the family and motherhood. I analyze how the practice of sending money and gifts challenges the state’s politics of traditional family and gender by examining how sending money and gifts frequently gains legitimacy with the migrant mothers’ claim of having a good family even though they do not adhere to traditional family norms.